Soil Burial Degradation and Morphology of PLA/Sugarcane Bagasse Biocomposites - Ahmad Hibatullah; Salahuddin Junus; Mochamad Asrofi; R. A. Ilyas (Green Engineering Society, 2026)
This study aimed to investigate the degradation behavior and surface morphology of polylactic acid (PLA) biocomposites reinforced with sugarcane bagasse fibers (SCBF). The biocomposites were fabricated using the vacuum bagging technique with fiber loadings of 0, 22, 24, and 26 wt%. Their performance was evaluated through a 21-day soil burial test, water solubility test, and surface morphology analysis using a digital optical microscope. The results revealed that the incorporation of sugarcane bagasse fibers enhanced the biodegradation rate of the PLA biocomposites under soil burial conditions. The highest weight loss (17.02%) was obtained for the biocomposite containing 26 wt% SCBF after 21 days of burial, which was attributed to microbial activity and the hygroscopic nature of the natural fibers. In contrast, the addition of SCBF reduced the water solubility of the biocomposites due to the formation of a denser fiber network within the PLA matrix, which restricted water penetration and improved structural integrity. Morphological observations confirmed surface degradation after soil burial, as evidenced by the formation of cracks, fissures, and voids on the biocomposite surface. Overall, the incorporation of sugarcane bagasse fibers effectively improved the biodegradability of PLA biocomposites while maintaining lower water solubility, highlighting their potential for environmentally friendly packaging applications.